DEVELOPING AND TESTING AN AIR FLOW DISTRIBUTOR OF SOLAR DRYER FOR DRYING MORINGA OLEIFERA IN ARID CLIMATE - Sufyan A Al-Mashhadany ,; M. K. Khedher Agha , (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate an air-flow distributer of a solar dryer. This study was contained two factors: First, the air outlet throttle (three angles, 30°, 60°, and 90°). Second, the design of the air inlet with three levels (new design (I2), without (I1), and half-opening air inlet gate of the new design (I3)). The results show significant effects on these parameters, where the highest efficiency (51.7%) was obtained at (I1) and (30°) angles. While the temperature changes between the inlet and outlet had a significant effect on the pressure difference, the pressure difference increased, reaching (1.65 Pa). Also, the drying rate was affected by the temperature and the amount of air entering the dryer. The highest drying rate gave (0.165 kg/h) when used the air discharge angle (30°) with the (I3), where this increased the temperatures of the air in the dryer reduced the air entering.